Use of Implementation Mapping With Community-Based Participatory Research: Development of Implementation Strategies of a New Goal Setting and Goal Management Intervention System - Kang, Eunyoung; Foster, Erin R. (Frontiers in Public Health, 2022)
Aims This study aims to identify implementation determinants, mechanisms of action, implementation strategies, and implementation outcome evaluation plans for a new theory-based rehabilitation goal setting and goal management intervention system, called MyGoals, using Implementation Mapping with community-based participatory research principles. Methods We completed Implementation Mapping tasks 1 to 4 as a planning team consisting of MyGoals target implementers (occupational therapists (OTs), MyGoals intervention target clients (adults with chronic conditions), and the research team. We are currently conducting mapping task 5. These processes were guided by the Consolidated Framework for Implementation Research, social cognitive theory, the taxonomy of behavior change methods, and Proctor's implementation research framework. Results We identified intervention-level determinants (MyGoals' evidence strength & quality, relative advantages) and OT-level determinants (knowledge, awareness, skills, self-efficacy, outcome expectancy). We selected the MyGoals implementation outcome (OTs will deliver MyGoals completely and competently), outcome variables (acceptability, appropriateness, feasibility, fidelity), and process outcomes. We also determined three performance objectives (e.g., OTs will deliver all MyGoals intervention components) and 15 change objectives (e.g., OTs will demonstrate skills for delivering all MyGoals intervention components). Based on the identified outcomes, objectives, and determinants, we specified the mechanisms of change (e.g., active learning). To address these determinants and achieve the implementation outcomes, we produced two tailored MyGoals implementation strategies: MyGoals Clinician Education and MyGoals Clinician Audit & Feedback. We developed evaluation plans to explore and evaluate how these two MyGoals implementation strategies perform using a mixed-methods study of OT-client dyads. Conclusion We produced tailored implementation strategies for a rehabilitation goal setting and goal management intervention by using Implementation Mapping with community-based participatory research principles. The MyGoals implementation strategies may help OTs implement high-quality goal setting and goal management practice and thus contribute to bridging current research-practice gaps. Our findings can provide insight on how to apply implementation science in rehabilitation to improve the development and translation of evidence-based interventions to enhance health in adults with chronic conditions.